Analisis Kualitas Pelayanan Karyawan Tunarungu di Deaf Café Gading Serpong - Ellan Jaya Adi Putra; Sri Pujiastuti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study examines the service quality of deaf employees at Deaf Café Gading Serpong using the SERVQUAL framework within the context of inclusive culinary tourism. A qualitative descriptive approach with a case study design was employed to capture in-depth service experiences. Data were collected through semi-structured in-depth interviews with eight customers selected via purposive sampling, complemented by passive participant observation and documentation. Data analysis followed the interactive model of Miles and Huberman, involving data reduction, data display, and conclusion drawing. The findings reveal that the tangibles dimension was positively perceived, reflected in the professional appearance of employees, clean service areas, and the availability of visual communication aids that supported the ordering process. Reliability was demonstrated through accurate order fulfillment with minimal errors. Responsiveness was evident in employees’ attentiveness and willingness to assist customers despite communication differences. Assurance emerged from employees’ competence and their ability to build customer trust through consistent service behavior. Empathy was identified as the most prominent dimension, shown through friendliness, patience, and heightened nonverbal attentiveness toward customers. Overall, hearing impairments did not hinder service quality; instead, they encouraged adaptive communication strategies and innovative service practices. This study contributes to the literature on inclusive tourism by highlighting how disability-friendly workplaces can deliver quality service, and it offers practical insights for culinary business managers seeking to implement inclusive and sustainable service models.